Optical Properties of Continuous and Pixelated Scintillation Crystals - Mikeli, M.; et al., ... (HNPS Advances in Nuclear Physics, 2020)
The optical photon distribution produced inside continuous and pixelated scintillation crystals by the absorption of a γ-ray have been studied with the photon transport program DETECT 2000. With this program the charge signals recorded by a multi-wired anode system, like the Position Sensitive PhotoMultiplier Tube (PSPMT) of a γ-Camera, are simulated. Based on the analytical parametrization which is fitted to experimental data, a new position reconstruction method for PSPMTs is proposed in this work. Planar images have been reconstructed with the new method and compared to the traditional charge center of gravity technique. Data are obtained from a small field, high resolution γ-Camera system with a multi- wired crossed anode using the R2486 (HAMAMATSU) PSPMT. Systematic studies for continuous and pixelated inorganic scintillation crystals of CsI(Tl) have been performed for different phantom geometries using small capillaries of 99mTc. The developed method seems to drastically improve the resolution of the reconstructed planar information, even when homogeneous crystals are used.